Child Passenger Safety Initiative for Primary Care Providers - Ribeiro, Laurie (My University, 2022)
Motor vehicle collisions are a leading cause of childhood injury and death. Primary care providers (PCP) have the potential to equip parents and caregivers with knowledge and education regarding the importance of child passenger safety (CPS). Evidence-based literature supports that increasing PCP knowledge of CPS and child safety seats (CSS) will increase the knowledge of caregivers. This shared knowledge, in turn, will promote childhood injury prevention. This quality improvement (QI) project implemented a CPS-focused educational initiative for PCPs. The initiative focused on PCPs increasing shared knowledge with caregivers through anticipatory guidance. The target population was individuals attending well-child visits from birth to eight years old. This intervention produced an increase in CPS-focused anticipatory guidance documented during well-child visits. Increased knowledge of CPS in the primary care setting has the potential to prevent childhood injury and death.
Keywords: Child passenger safety; Primary care; Childhood injury prevention; Motor vehicle collision; Pediatric; Anticipatory guidance